Możliwości i ograniczenia działalności animacyjnej w gminnych ośrodkach kultury - Lewartowicz, Urszula (Adult Education Discourses, 2020)
This article is devoted to institutional animation activities in rural environments. It presents the results of free interviews conducted with directors of communal cultural centers operating in the Lublin Voivodeship. The study focuses on the opportunities, barriers and challenges associated with the institutional model of socio-cultural animation. Based on the collected research material, the animation resources of rural environments (community, creativity, practicality, local cultural heritage, social ties, the socio-cultural potential of leaders) and the most important barriers hindering animation activities (political, economic, spatial, infrastructural, mentality) were identified and characterized. The statements of the directors cited in the article reveal their individual visions of cultural activities as well as the possibilities and limitations associated with them.